The effects of accountability on the allocation of school resources: Regression discontinuity evidence from Chile - Gregory Elacqua; Analía Jaimovich; Alonso Román (Inter-American Development Bank (IDB), 2019)
This research examines the effect of accountability threats for low performing schools on resource allocation decisions and provides evidence that schools act with strategic behavior only when the accountability pressure is high. We used a generalization of a traditional regression discontinuity design, taking advantage of the sharp discontinuity in the Chilean accountability system's ranking of schools based on performance measures, and of a unique school level expenditure data set, to make causal estimates of the effect of being ranked as "low-performing" on school spending decisions. The results indicate that, while first time low-performing schools do not change their resource allocation strategy, chronically underperforming schools are more likely to hire external technical pedagogical support and invest in teacher training that may help them boost achievement in the short and medium-term and avoid sanctions.
Keywords: I22; I28; H52; 330; School accountability; school spending; school finance; Chile; vouchers